1952
DOI: 10.1172/jci102695
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of Mechanical Exsufflation on Experimental Obstructive Breathing in Human Subjects 1

Abstract: The increased physical effort necessary to breathe through a constricted orifice results in an instantaneous and uncomfortable sensation of dyspnea. The immediate sensation of difficulty in breathing is aroused by proprioceptive reflexes. The duration of inspiration and expiration becomes markedly prolonged, (1, 2) and in spite of the increased work entailed, the peak volume flow rates diminish. The minute ventilation has been shown by Cain and Otis (1) to decrease. Haldane and Priestley (3) and others (1, 4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1953
1953
1958
1958

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This might be explained by the ability of the exsufflator both to overcome obstruction to breathing (9) and to ventilate the alveoli more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the ability of the exsufflator both to overcome obstruction to breathing (9) and to ventilate the alveoli more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…According to Macintosh and Mushin (1947), in an adult breathing 8 litres per minute quietly, the maximum flow rate of air during normal inspiration reaches 25 litres per minute, and they use this latter rate to measure experimentally the resistance of endotracheal connectors. This figure may be on the low side, however, as Proctor and Hardy (1949) found an average peak inspiratory velocity (in normal patients) of 35 litres per minute; similarly Cherniack et al (1952) give a figure of 35.5 litres per minute, and Mead and Whittenberger (1953) 30-50 litres per minute for quiet breathing.…”
Section: The Theory Of Resistancementioning
confidence: 94%
“…This device has proved useful in the treatment of cases with chronic bronchial infection, and has been applied successfully to patients with respiratory paralysis undergoing artificial respiration in tank respirators. Cherniack et al (1952) have also demonstrated physiological advantages of this effect, particularly in obstructed breathing.…”
mentioning
confidence: 99%